2006
DOI: 10.1590/s0100-19652006000300009
|View full text |Cite
|
Sign up to set email alerts
|

O enfoque social da segurança da informação

Abstract: ResumoO uso cada vez mais disseminado de sistemas informatizados integrados por meio de redes é um fato determinante da sociedade da informação. Este universo de conteúdos e continentes digitais está sujeito a várias ameaças que comprometem seriamente a segurança do complexo usuário-sistema-informação. A tecnologia da informação é capaz de apresentar parte da solução a este problema, mas não é capaz de resolvê-lo integralmente. As políticas de segurança da informação devem contemplar o adequado equilíbrio dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…People are regarded as the greatest weakness of Information Security (Mitnick & Simon, 2003;Silva & Stein, 2007;Sêmola, 2014). For this reason, information protection should not be only a technical issue, but also social, for which there is no purely technological solution known (Marciano & Lima-Marques, 2006). Therefore, measures should address not only technological and physical issues but also administrative, to change human behavior in the organization.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…People are regarded as the greatest weakness of Information Security (Mitnick & Simon, 2003;Silva & Stein, 2007;Sêmola, 2014). For this reason, information protection should not be only a technical issue, but also social, for which there is no purely technological solution known (Marciano & Lima-Marques, 2006). Therefore, measures should address not only technological and physical issues but also administrative, to change human behavior in the organization.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, information security should be treated based on theories that help to understand it from a social perspective, as proposed by Dhillon and Backhouse (2001), Björck (2004Björck ( , 2005, Marciano and Lima-Marques (2006) Albrechtsen (2008) and Coles-Kemp (2009). Besides, the adoption of Information Security measures must be addressed by a theory that considers the influence of external factors, which is consistent with the Institutional Theory (Kam, Katerattanakul, Gogolin, & Hong, 2013), a theoretical approach that is common in studies of social sciences and suggested for studies on Information Security by different authors, such as Björck (2004), Kam et al (2013) and .…”
Section: Information Security Governancementioning
confidence: 99%
“…A pesquisa "Segurança da Informaçãouma abordagem social" [18] e [19] faz referencia ao caráter social da segurança da informação, em um momento em que as redes sociais estão a cada dia mais inseridas no cotidiano das pessoas e das corporações, traz à tona a importância da preparação dos usuários para a obtenção de uma segurança da informação de qualidade, e apresenta a segurança da informação como um domínio multidisciplinar para as ciências sociais.…”
Section: Trabalhos Correlatosunclassified
“…O processo investigativo pode continuar ciclicamente para que as hipóteses sejam confirmadas ou corroboradas, segundo Popper. Entretanto, todas estas etapas estão sujeitas à riscos de segurança, que podem ocorrer em diversos deste ciclo de vida (MARCIANO, 2006). O ciclo de vida em Segurança da Informação deve criar uma camada de proteção de forma que o ciclo de vida proposto pela Ciência da Informação não sofra com possíveis ameaças.…”
Section: Metodologiaunclassified